Teachers Beliefs and Practices on Teaching Speaking Using English Songs - Adela Oktami (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
Abstract     To know about the teachers’ beliefs on teaching speaking using English songs, the teaching plans prepared before starting to teach using English songs, the process of teaching, and teachers assess students after teaching using English songs. This study used the Qualitative paradigm research method and design of this research was a case study. This study's subjects were two English teachers at SMPN 3 Tewang Sangalang Garing. The instrument in this study were; observations (field-note) Questionnaire and interview with the English teachers. The data were analyzed by reducing, analyzing, and concluding. The research found the teacher believes in the use of English song media, it is clear from how the teacher applies it during the learning process in the classroom, can concluded the teachers’ process used three stages (a) opening, (b) main activity, and (c) closing. Teachers also believe that the use of English song media is very effective, but they also claim that all the media used are very effective, it's just that there are differences when using song media and not. It was found that using the media song students became more enjoy, happy, not bored in class, easier to understand explanations and able to speak more fluently. However, teachers also face difficulties and challenges in using the song media because of the limited school facilities.